SÍNTESE E CARACTERIZAÇÃO ÓPTICA E ESTRUTURAL DE CRISTAIS DE KCl PARA APLICAÇÕES EM CÉLULAS SOLARES - AMORIN, Paula Vitória; FINOTO, Simone; FINOTO, Simone; ANDRADE, Luis Humberto da Cunha; ANDRADE, Luis Humberto da Cunha (ANAIS DO ENIC, 2018)
-